Phonetic detail in German syllable pronunciation: influences of prosody and grammar - Samlowski, Barbara; Möbius, Bernd; Wagner, Petra (Frontiers in Psychology, 2014)
This study presents two experiments designed to disentangle various influences on syllable pronunciation. Target syllables were embedded in carrier sentences, read aloud by native German participants, and analyzed in terms of syllable and vowel duration, acoustic prominence, and spectral similarity. Both experiments revealed a complex interaction of different factors, as participants attempted to disambiguate semantically and syntactically ambiguous structures while at the same time distinguishing between important and unimportant information. The first experiment examined German verb prefixes that formed prosodic minimal pairs. Carrier sentences were formulated so as to systematically vary word stress, sentence focus, and the type of syntactic boundary following the prefix. We found clear effects of word stress on duration, prominence, and spectral similarity as well as a small influence of sentence focus on prominence levels of lexically stressed prefixes. While sentence boundaries were marked by particularly high prominence and duration values, hardly any effect was shown for word boundaries. The second experiment compared German function words which were segmentally identical but appeared in different grammatical roles. Here, definite articles were found to be shorter than relative pronouns and still shorter than demonstrative pronouns. As definite articles are also much more common than the other two lexical classes, effects of lemma frequency might also have played a role.